How Does Childhood Chronic Renal Disease Impact Upon Family Life? A Systematic Review. - Connole, Kate (2013)
Introduction and Background The number of children living with chronic illnesses is on the increase due to improved medical advances, medications and treatment. One of these illnesses is chronic renal disease, which is caused by the kidneys deteriorating over time and is permanent. Chronic renal failure can only be treated by renal replacement therapy, which includes peritoneal dialysis, haemodialysis and transplantation. Review Question and Methodology The current systematic review aimed to answer the following research question; ‘How does childhood chronic renal disease impact upon family life?’ An electronic search of CINAHL and MEDLINE (OVID) databases were conducted using the University of Nottingham eLibrary Gateway. The electronic search lasted four months. A structured search strategy was devised, and incorporated key words. Once studies had been retrieved, they were filtered using clear inclusion/exclusion criteria. 7 studies were indentified as being appropriate to use in the review, following this, their data was extracted, critically analysed and synthesised in narrative summaries. Results From the included studies, the following themes were extracted; the effect childhood chronic renal failure has on healthy siblings, support systems used by parents, coping strategies of parents, changing roles amongst family members and mothers as the main caregivers. Conclusion VII In conclusion, childhood chronic renal disease impacts significantly upon family life in that the lived experience of parents and healthy siblings is affected. The role of parent is intensified and altered when caring for a child with chronic renal failure as parents and mainly mothers, become the child’s main caregiver. Siblings are affected by childhood chronic renal failure in that their lives become disrupted due to the family routine evolving to fit around the care of their ill sibling.